Physicochemical Properties of Hydrated Portland Cement Blended with Rice Husk Ash - Joseph Mwiti Marangu; Cyprian Muturia M’thiruaine; Mark Bediako (Journal of Chemistry)
In the presence of significant quantities of carbon dioxide (CO2) and elevated temperatures in the atmosphere due to climate change, cement-based materials are susceptible to carbonation. Blended cements are more prone to carbonation attack than Portland cement. There is a need to evaluate the carbonation resistance of blended cements in a carbonation-prone environment. This paper presents experimental findings obtained from an evaluation of carbonation resistance tests on Rice Husk Ash- (RHA-) blended cement. The blended cement was made by intergrinding of Portland Cement (PC) and RHA to make the test cement (PC-RHA). The RHA dosage in the PC-RHA was varied from 0 to 30% by mass of PC. Pozzolanicity, standard consistency, and setting time tests were conducted on PC-RHA. Mortar prisms measuring 160 mm × 40 mm x 40 mm were separately cast at a water/cement ratio (w/c) of 0.50 and 0.60 and cured in water for 2, 7, 14, 28, and 90 days. Compressive strength tests were conducted on the mortar prisms at each of the testing ages. The prepared mortars were also subjected to accelerated carbonation tests in two Relative Humidity (RH) curing regimes, one maintained at an RH greater than 90% and the other between 50–60%. Carbonation resistance of the mixtures was evaluated in terms of the changes in carbonation depth using a phenolphthalein test at the age of 7, 14, 28, and 56 days of curing in a continuous flow of CO2. Compressive strength measurements were also taken during each of the carbonation testing ages. For comparison, similar tests were conducted using commercial PC. The results showed that PC-RHA was pozzolanic while PC was nonpozzolanic. Higher water demand and longer setting times were observed in PC-RHA than in PC. Moreover, there was increased strength development in water-cured samples with increased curing duration. Carbonation results indicated that there was a marked increase in carbonation depth with increased dosage of RHA in PC-RHA binders, increased duration of exposure to CO2, and decreased RH (RH between 50–60%). PC-RHA binders exhibited lower carbonation resistance than PC. In conclusion, for mortars at any w/c ratio, carbonation resistance decreased with increase in RHA dosage and increased w/c ratio.